Agar and activated charcoal influence the in vitro development of shoot and root sequoia - Meneguzzi, Aline; Camargo, Samila Silva; Navroski, Marcio Carlos; Pereira, Mariane de Oliveira; Souza, Patricia Fukushima; Rufato, Leo (Revista de Ciências Agroveterinárias, 2020)
Experimental seedlings with Sequoia sempervirens (Lamb), a species known worldwide for its large size, longevity and quality of timber, are beginning in Brazil, making the availability of quality seedlings necessary. Thus, the technique of tissue culture, via micropropagation, becomes a great ally for the guarantee of genetic superiority, large-scale production and reduced propagation time. Currently there are numerous protocols for several species, however, it is necessary to verify all influential agents in the success of in vitro development. The objective of this work was to determine the influence of activated charcoal and agar concentrations on aerial and root development of S. sempervirens. The treatments involved the presence / absence of activated carbon (1 g L-1), combined with concentrations of agar (4, 5 and 6 g L-1) in 50% MS medium. For the number and length of shoots and roots, only activated carbon was significant, and the presence benefited the development of the explants. For the percentage of callus, there was interaction of the factors, and higher concentrations of agar (5 and 6 g L-1) in the presence of medium were harmful, since they presented higher callosity, which minimizes the rooting rates. It is indicated the addition of activated charcoal (1 g L-1) and lower concentration of agar (4 g L-1) in 50% MS culture medium for a better in vitro development of sequoia.